Beyond Entertainment: Modern Slavery in Nepal’s Cabin Restaurants and Massage Parlors - Kafle, Sirjana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Women and girls in Nepal face systemic, structural gender discrimination and extreme poverty, driving them into high-risk employment in Kathmandu Valley’s entertainment sector (cabin/dohori restaurants, massage parlors). Following the collapse of Nepal’s carpet/garment industries, these unregulated venues became primary employers for economically desperate, women and girls—often operating as fronts for exploitation. Objectives: This study assessed the prevalence of modern slavery "red flags" (fraudulent recruitment, coercion, economic exploitation, restricted freedom) and documented workers’ lived experiences to identify pathways for improving their safety and autonomy. Methods: A mixed-methods approach combined quantitative surveys and qualitative in-depth interviews with female workers. Purposive sampling targeted venues across Kathmandu Valley. Rigorous ethical protocols ensured confidentiality and voluntary participation. Findings: • 71% experienced fraudulent recruitment; 59% earned <2/day; 76% worked >8 hours. • Sexual coercion was endemic: 90% harassed by customers, 48% by owners, 73% forced into "additional duties" (including sex acts). • Freedom restrictions: 40% felt unable to quit; 30% could not protest abuses; 64% feared requesting wage increases. • 33% of workers were minors (<18 years); 29% were forced into prostitution. • 73% expressed profound job dissatisfaction but lacked alternatives. Conclusion: The convergence of deceptive recruitment, economic violence, sexual coercion, and restricted agency meets international definitions of modern slavery, with minors disproportionately exploited. Implications: Urgent action is needed: (1) enforce anti-trafficking laws against owners, (2) expand survivor-centered support (healthcare, legal aid, shelters), (3) create ethical livelihood alternatives, and (4) implement sector-wide labor inspections and contracts.